Acta stomatologica Croatica and PubMed Central - Hrvoje Brkić (University of Zagreb. School of Dental Medicine, 2016)
April 15 2016 marked the 50th anniversary of continuous publishing of the journal Acta stomatologica Croatica (ASCRO). The celebration was held in the great hall of the Croatian Medical Association, with numerous guests from the biomedical field. The history of the journal was presented by Goran Knežević (editor-in-chief 1996-2006) and Hrvoje Brkić (current editor-in-chief), who presented all the current information on the electronical editing and its current indexation. Only a few days later, the Editorial Office received the information that ASCRO has been included in PubMed Central since volume 48, an impulse for the members of the Editorial Board and the Editor-in-Chief to make ASCRO better and more cited.